Silage Production from Corn Stalks at the Cattle Farm CV. Pelita Samondung Agro Sumenep - Putri, Kanza Nabilah; Zaman, Moh. Qomarus (Bioconsortium : Biological Research and Education, 2024)
Providing quality and sustainable feed is very important for the growth and development of cattle. Silage is a livestock feed that is deliberately stored and preserved by fermentation process with the intention of obtaining feed ingredients that are still high quality and durable so that they can be given to livestock when there is a shortage of feed. This study aims to determine the process of making silage from corn trees at the CV. Pelita Samondung Agro cattle farm. This study uses a qualitative descriptive method with interviews and direct manufacturing practices. Based on the results of the study, the silage production process at the Pelita Samondung Agro cattle farm still uses conventional methods using easily available materials such as corn straw, rice powder and molasses and using a shredder to cut the corn straw. Mixing all ingredients and the fermentation process for 21 days in an airtight container is a key process in making silage on this farm. After the fermentation process is complete, the feed ingredients will change color to yellow and produce a pungent sour odor. The making of silage feed is said to be successful if the fermented material is not moldy and smells sour.